Pelatihan Desain Grafis Canva bagi Siswa SDN Jabon 1 Banyakan Kediri - Iqlima Zahari; Galuh Wilujeng Saraswati; Ardiawan Bagus Harisa; Joel Justin Adrian; Mandasari Kusuma Dyah Tantri; Adelia Rahmawati; Wildan Mahmud; Agus Winarno (Lembaga Pengembangan Kinerja Dosen, 2025)
Graphic design is a communication process that uses visual elements, such as writing, shapes and images that are intended to create a perception of a message to be conveyed. Canva is an online graphic design application that can be used to design various types of designs, including presentations, resumes, posters, brochures, booklets, graphs, infographics, banners, markers, bulletins and so on. At SDN Jabon 1, computer learning, especially design, is included in extracurricular activities, due to limited facilities, so that learning is less than optimal. Graphic design training at SD Jabon 1 aims to equip students with graphic design skills. The stages of implementing community service activities that we carry out are preparation, opening, delivering materials, questions and answers, practice, evaluation, closing. The results of this community service activity are: The training activity went smoothly, attended by 30 participants, students were able to follow the creation of graphic designs practiced by the instructor and were able to design based on the instructor's direction. Students were able to design posters independently, knowledge and understanding of Canva graphic design and how to make it increased, used as a means to channel students' creativity and as a form of early technology adaptation. With this training, students are happy because they gain new knowledge about Canva.